Head first design patterns. - Freeman, Eric, 1965-; Freeman, Elizabeth, 1966-2024 (Beijing : O'Reilly, 2004)
1 Welcome to design patterns : an introduction 2 Keeping your objects in the know : the observer pattern 3 Decorating objects : the decorator pattern 4 Baking with OO goodness : the factory pattern 5 One of a kind objects : the Singleton pattern 6 Encapsulating invocation : the command pattern 7 Being adaptive : the adapter and facade patterns 8 Encapsulating algorithms : the template method pattern 9 Well-managed collections : the iterator and composite patterns 10 The state of things : the state pattern 11 Controlling object access : the proxy pattern 12 Patterns of patterns : compound patterns 13 Patterns in the real world : better living with patterns 14 App. : leftover patterns